1990
DOI: 10.1128/mcb.10.4.1769
|View full text |Cite
|
Sign up to set email alerts
|

mRNAs that mature through trans-splicing in Caenorhabditis elegans have a trimethylguanosine cap at their 5' termini.

Abstract: Approximately 10% of the mRNAs in the nematode Caenorhabditis elegans mature through a trans-splicing mechanism that involves the transfer of a 22-nucleotide spliced leader to the 5' end of the pre-mRNA. The spliced leader RNA exists as a small nuclear ribonucleoprotein particle and has the trimethylguanosine cap that is characteristic of eucaryotic small nuclear RNAs. We found that the trimethylguanosine cap present on the spliced leader RNA was transferred to the pre-mRNA during the trans-splicing reaction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
47
0
2

Year Published

1992
1992
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 24 publications
2
47
0
2
Order By: Relevance
“…This modification is of particular interest because the mRNAs of some lower metazoans contain mRNAs of two types, those containing m 7 GTP and those containing m 3 2,2,7 GTP. mRNAs from ∼70% of the genes in Caenhorabditis elegans contain the m 3 2,2,7 Gp 3 G cap due to trans-splicing (Liou and Blumenthal 1990;van Doren and Hirsh 1990;Zorio et al 1994). In the present study, we found that m 3 2,2,7…”
Section: Inhibition Of Cap-dependent Translationsupporting
confidence: 64%
“…This modification is of particular interest because the mRNAs of some lower metazoans contain mRNAs of two types, those containing m 7 GTP and those containing m 3 2,2,7 GTP. mRNAs from ∼70% of the genes in Caenhorabditis elegans contain the m 3 2,2,7 Gp 3 G cap due to trans-splicing (Liou and Blumenthal 1990;van Doren and Hirsh 1990;Zorio et al 1994). In the present study, we found that m 3 2,2,7…”
Section: Inhibition Of Cap-dependent Translationsupporting
confidence: 64%
“…Our findings suggest that PIMT expression increases the amount of TMG-containing unspliced/partially spliced HIV-1 RNAs that are then exported through the CRM-1 pathway and expressed into the corresponding proteins in the cytoplasm. Compatible with our results, in Caenorhabditis elegans and Ascaris lumbricoides, nematode mRNAs can acquire TMG caps by transsplicing, and in these settings, virtually all actin and ribosomal protein mRNAs are TMG-capped and loaded onto polysomes and are functionally translated with efficiency (59)(60)(61). Similarly, during the replication of togaviruses (e.g., Semliki Forest virus and Sindbis virus), late viral mRNAs acquire hypermethylated guanosine caps, and the expression of late proteins is proficient (21,22).…”
Section: Discussionmentioning
confidence: 50%
“…Although not closely related, these nematodes both add the canonical SL1 spliced leader to the majority of their mRNAs (Maroney et al 1995). Biochemical and molecular genetic investigations have built up a detailed picture of the mechanism and biological significance of spliced leader addition to mRNA in nematodes (Bruzik et al 1988;Thomas et al 1988;Maroney et al 1990a,b;Van Doren and Hirsh 1990;Denker et al 1996Denker et al , 2002Ferguson et al 1996;Ferguson and Rothman 1999;Lall et al 2004;Cheng et al 2007;MacMorris et al 2007). The conservation of the SL1 primary sequence between C. elegans and A. suum suggests a functional constraint.…”
Section: Discussionmentioning
confidence: 99%